INVESTIGASI KARAKTERISTIK TANAH MENGGUNAKAN METODE HORIZONTAL TO VERTICAL SPECTRAL RATIO PADA STUDI KASUS KAWASAN INSTITUT TEKNOLOGI SUMATERA - Syafitri, Meta Nisrina; Antika Pratiwi; Ulya Nur Afifah (Journal of Innovation Research and Knowledge, 2025)
Institut Teknologi Sumatera (ITERA), located in South Lampung Regency, near to the Sunda subduction zone, which has earthquake hazard potential. This study investigates soil characteristics in the ITERA area using the Horizontal to Vertical Spectral Ratio (HVSR) method, based on 2023 microtremor data from 30 measurement points. Analysis focused on dominant frequency (f0), amplification factor (A0), and seismic vulnerability index (Kg) to evaluate subsurface variations and earthquake-induced damage potential. Results show dominant frequencies ranging from 0.52 to 17 Hz. The northwest and central zones, with values below 2 Hz, suggest thick and soft tuff sediments, whereas higher values of 7-17 Hz in the northeast and southeast indicate thinner, compact soil. Amplification factors vary between 1 and 7, with lower values in the central–northern zones and higher ones in the south. The seismic vulnerability index ranges from 0.2 to 40, with the southwest and southern areas exhibiting the highest values (20-40). These findings refine previous studies by offering better spatial resolution and highlight critical areas for earthquake risk mitigation and infrastructure planning